2020
DOI: 10.1073/pnas.1913042117
|View full text |Cite
|
Sign up to set email alerts
|

Diet modulates brain network stability, a biomarker for brain aging, in young adults

Abstract: Epidemiological studies suggest that insulin resistance accelerates progression of age-based cognitive impairment, which neuroimaging has linked to brain glucose hypometabolism. As cellular inputs, ketones increase Gibbs free energy change for ATP by 27% compared to glucose. Here we test whether dietary changes are capable of modulating sustained functional communication between brain regions (network stability) by changing their predominant dietary fuel from glucose to ketones. We first established network st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 59 publications
(47 reference statements)
3
92
0
Order By: Relevance
“…Extending the observation window beyond 120 min in the basal state may reveal the addition of circulating BDNF from genomic sources, as demonstrated in non-human models ( Marosi et al, 2016 ; Sleiman et al, 2016 ; Hu et al, 2018 ). Interestingly, as we were preparing this manuscript, Mujica-Parodi et al (2020) reported a series of brain imaging studies showing that an acute ketone bolus improves brain network stability compared to acute glucose bolus. These findings have implications for aging and brain-health optimization, as reductions in brain network stability relate to decreased brain activity and lower cognitive function ( Mujica-Parodi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending the observation window beyond 120 min in the basal state may reveal the addition of circulating BDNF from genomic sources, as demonstrated in non-human models ( Marosi et al, 2016 ; Sleiman et al, 2016 ; Hu et al, 2018 ). Interestingly, as we were preparing this manuscript, Mujica-Parodi et al (2020) reported a series of brain imaging studies showing that an acute ketone bolus improves brain network stability compared to acute glucose bolus. These findings have implications for aging and brain-health optimization, as reductions in brain network stability relate to decreased brain activity and lower cognitive function ( Mujica-Parodi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, as we were preparing this manuscript, Mujica-Parodi et al (2020) reported a series of brain imaging studies showing that an acute ketone bolus improves brain network stability compared to acute glucose bolus. These findings have implications for aging and brain-health optimization, as reductions in brain network stability relate to decreased brain activity and lower cognitive function ( Mujica-Parodi et al, 2020 ). However, it has yet to be determined if circulating BDNF is involved in these and other improvements in brain health with KME ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…A collaboration between Stony Brook and Oxford Universities showed that both ketogenic diets and exogenous ketones (ketone monoester) improve network stability in young healthy individuals. By contrast, standard Western diets and glucose decrease network stability ( Mujica-Parodi et al, 2020 ). These data are consistent with the hypothesis that ketogenic interventions could prevent neurodegenerative disease and cognitive decline, as has been demonstrated in mice ( Roberts et al, 2017 ).…”
Section: Ketotherapeuticsmentioning
confidence: 99%
“…Third, fasting and ketogenic diets share the common feature of stimulating hepatic production of the ketone body, β-hydroxybutyrate, which itself is a signaling molecule that regulates mTORC1 ( Li et al, 2017 ; Newman and Verdin, 2017 ; Norwitz et al, 2019a ). Interestingly, it has recently been demonstrated that both short-term ketogenic diets and acute administration of exogenous β-hydroxybutyrate improve a marker of brain aging called “brain network stability,” in contrast to standard Western diets and sugar which decrease network stability ( Mujica-Parodi et al, 2020 ). Long-term prospective studies will need to be conducted to determine whether fasting and ketogenic diets are truly neuroprotective in humans.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%